Effects of mechanical strain on periodontal ligament fibroblasts in presence of Aggregatibacter actinomycetemcomitans lysate - Agnes Schröder; Julia Stumpf; Eva Paddenberg; Patrick Neubert; Valentin Schatz; Josef Köstler; Jonathan Jantsch; James Deschner; Peter Proff; Christian Kirschneck (BMC, 2021)
Abstract Purpose Many adult orthodontic patients suffer from periodontitis, which is caused by oral pathogens such as the gram-negative Aggregatibacter actinomycetemcomitans (Agac). Like orthodontic tooth movement, periodontitis is associated with inflammation and alveolar bone remodelling thereby affecting orthodontic treatment. Interactions of both processes, however, are not sufficiently explored, particularly with regard to oxidative stress. Methods After preincubation with Agac lysate for 24 h periodontal ligament fibroblasts (PDLF) were either stretched or compressed for further 48 h simulating orthodontic forces in vitro. We analysed the expression of genes and proteins involved in the formation of reactive oxygen species (NOX-4, ROS) and nitric oxide (NOS-2), inflammation (TNF, IL-6, PTGS-2) and bone remodelling (OPG, RANKL). Results Agac lysate elevated the expression of NOX-4, NOS-2, inflammatory IL-6 and PTGS-2 and the bone-remodelling RANKL/OPG ratio during compressive, but not tensile mechanical strain. Agac lysate stimulated pressure-induced inflammatory signalling, whereas surprisingly ROS formation was reduced. Pressure-induced downregulation of OPG expression was inhibited by Agac lysate. Conclusions Agac lysate impact on the expression of genes and proteins involved in inflammation and bone remodelling as well as ROS formation, when PDLF were subjected to mechanical forces occurring during orthodontic tooth movement.